Clinical trials of medicinal products in pregnant women (overview) - Diusembaeva, N.K.; Kalieva, Sh.S.; Yukhnevich Е.А.; Miasnikov, Zh.V. (Fundamental and Experimental Biology, 2022)
The article provides an overview of the necessity and ethical issues associated with clinical trials of medicines in pregnant women. Despite a constant increase in the proportion of women who use drugs during pregnancy, pregnant women are still excluded from drug trials, and there is a large scientific gap requiring a significant increase in drug research during pregnancy. However, there are serious challenges in conducting these drug trials in pregnancy.